You are on page 1of 20

# Applications of

Differential Equations

19.4

Introduction
Sections 19.2 and 19.3 have introduced several techniques for solving commonly occurring rst-order
and second-order ordinary dierential equations. In this Section we solve a number of these equations
which model engineering systems.

'

## understand what is meant by a dierential

equation

Prerequisites
Before starting this Section you should . . .

## be familiar with the terminology associated

with dierential equations: order, dependent
variable and independent variable
be able to integrate

&
'

%
\$

## recognise and solve rst-order ordinary

dierential equations, modelling simple
electrical circuits, projectile motion and
Newtons law of cooling

Learning Outcomes
On completion you should be able to . . .

&
HELM (2005):
Section 19.4: Applications of Dierential Equations

## recognise and solve second-order ordinary

dierential equations with constant
coecients modelling free electrical and
mechanical oscillations
recognise and solve second-order ordinary
dierential equations with constant
coecients modelling forced electrical and
mechanical oscillations

51

## 1. Modelling with first-order equations

Applying Newtons law of cooling
In Section 19.1 we introduced Newtons law of cooling. The model equation is
d
= k( s )
= 0 at t = 0.
(5)
dt
where = (t) is the temperature of the cooling object at time t, s the temperature of the
environment (assumed constant) and k is a thermal constant related to the object, 0 is the initial
temperature of the liquid.
Task

d
= k( s ),
dt

= 0

at t = 0

Your solution

Answer


d
=
s


k dt

## Now integrate both sides of this equation:

Your solution

Answer
ln( s ) = kt + C where C is constant
Apply the initial condition and take exponentials to obtain a formula for :
Your solution

Answer
ln(0 s ) = C. Hence ln( s ) = kt+ln(0 s )
Thus, rearranging and inverting, we nd:


s
s
= ekt
= kt

ln
0 s
0 s
52

so that

ln( s )ln(0 0 ) = kt

giving = s + (0 s )ekt .
HELM (2005):
Workbook 19: Dierential Equations

## The graph of against t for = s + (0 s )ekt is shown in Figure 4 below.

s
t

Figure 4
We see that as time increases (t ), then the temperature of the object cools down to that of
the environment, that is: s .
We could have solved (5) by the integrating factor method, which you are now asked to do.
Task

d
+ k = ks ,
dt

= 0 at t = 0

(6)

## State the integrating factor for this equation:

Your solution

Answer

e k dt = ekt is the integrating factor.
Multiplying (6) by this factor we nd that
d kt
d
+ kekt = ks ekt
(e ) = ks ekt
or, rearranging,
dt
dt
Now integrate this equation and apply the initial condition:
ekt

Your solution

Answer
Integration produces ekt = s ekt + C, where C is an arbitrary constant. Then, applying the initial
condition: when t = 0, 0 = s + C so that C = 0 s gives the same result as before:
= s + (0 s )ekt ,
HELM (2005):
Section 19.4: Applications of Dierential Equations

53

## Modelling electrical circuits

Another application of rst-order dierential equations arises in the modelling of electrical circuits.
In Section 19.1 the dierential equation for the RL circuit in Figure 5 below was shown to be
di
+ Ri = E
dt
in which the initial condition is i = 0 at t = 0.
L

L
E
+

Figure 5
dy
First we write this equation in standard form { + P (x)y = Q(x)} and obtain the integrating
dx
factor.
Dividing the dierential equation through by L gives
E
di R
+
i=
dt L
L

## which is now in standard form. The integrating factor is e L dt = eRt/L .

Multiplying the equation in standard form by the integrating factor gives
di
R
E
+ eRt/L i = eRt/L
dt
L
L
or, rearranging,
eRt/L

E
d Rt/L
i) = eRt/L .
(e
dt
L
Now we integrate both sides and apply the initial condition to obtain the solution.
Integrating the dierential equation gives:
E Rt/L
e
+C
R
where C is a constant so
E
i = + CeRt/L
R
Applying the initial condition i = 0 when t = 0 gives
eRt/L i =

E
+C
R
E
so that C = .
R
E
Finally, i = (1 eRt/L ).
R
E
Note that as t , i
so as t increases the eect of the inductor diminishes to zero.
R
0=

54

HELM (2005):
Workbook 19: Dierential Equations

Task

A spherical pill with volume V and surface area S is swallowed and slowly dissolves
in the stomach, releasing an active component. In one model it is assumed that
the capsule dissolves in the stomach acids such that the rate of change in volume,
dV
, is directly proportional to the pills surface area.
dt
dV
= kV 2/3 where k is a positive real constant and solve this
(a) Show that
dt
given that V = V0 at t = 0.
(b) Experimental measurements indicate that for a 4 mm pill, half of the volume
has dissolved after 3 hours. Find the rate constant k (m s1 ).
(c) Estimate the time required for 95% of the pill to dissolve.

(a) First write down the formulae for volume of a sphere (V ) and surface area of a sphere (S) and
so express S in terms of V by eliminating r:
Your solution

Answer
4
V = r3
3

S = 4r2


3V
4

1/3
so

for constant k.

Your solution

Answer
dV
= kV 2/3
dt

## (negative to represent a decrease with time)

HELM (2005):
Section 19.4: Applications of Dierential Equations

55

## Using the condition V = V0 when t = 0, solve the dierential equation:

Your solution

Answer
Solving by separation of variables gives
1/3

1
(C kt)
V =
3
and setting V = V0 when t = 0 means
 3
1
1/3
V0 =
so C = 3V0
and the solution is
C
3

3
kt
1/3
V = V0
3
(b) Impose the condition that half the volume has dissolved after 3 hours to nd k:
Your solution

Answer
V =


1/3
V0

kt

and when t = 3, V =


56

V0
2

1/3
1/3

= V0

3

V0
so
2
k

and so

1/3

k = V0 (1 (0.5)1/3 )

HELM (2005):
Workbook 19: Dierential Equations

(c) First write down the solution to the dierential equation inserting the value of k obtained in (b)
and then use it to estimate the time to 95% dissolving:
Your solution

Answer
V =


1/3
V0

1/3
V0 (1

(0.5)

1/3

t
)
3

3

V = V0 1 (1 (0.5)

1/3

i.e.

## When 95% dissolved V = 0.05V0 so


3
1/3 t
0.05V0 = V0 1 (1 (0.5) )
so
3
so


1 (0.05)1/3
9.185 9 hr 11 min
t=3
1 (0.5)1/3

t
)
3

(0.05)1/3 = 1 (1 (0.5)1/3 )

3

t
3

## 2. Modelling free mechanical oscillations

Consider the following schematic diagram of a shock absorber:
Mass
Spring
Dashpot

Figure 6
The equation of motion can be described in terms of the vertical displacement x of the mass.
dx
Let m be the mass, k
the damping force resulting from the dashpot and nx the restoring force
dt
resulting from the spring. Here, k and n are constants.
Then the equation of motion is
HELM (2005):
Section 19.4: Applications of Dierential Equations

57

d2 x
dx
nx.
= k
2
dt
dt
Suppose that the mass is displaced a distance x0 initially and released from rest. Then at t = 0,
dx
= 0. Writing the dierential equation in standard form gives
x = x0 and
dt
dx
d2 x
+ nx = 0.
m 2 +k
dt
dt
We shall see that the nature of the oscillations described by this dierential equation depends crucially
upon the relative values of the mechanical constants m, k and n. This will be explored in subsequent
Tasks.
m

Task

## Find and solve the auxiliary equation of the dierential equation

m

dx
d2 x
+k
+ nx = 0.
2
dt
dt

Your solution

Answer
Putting x = et , the auxiliary equation is

k k 2 4m n
.
Hence =
2m

m 2 + k + n = 0.

The value of k controls the amount of damping in the system. We explore the solution for various
values of k.

Case 1: No damping
If k = 0 then there is no damping. We expect, in this case, that once motion has started it will
continue for ever. The motion that ensues is called simple harmonic motion. In this case we have


4m n
n
=
, that is, =
i
where i2 = 1.
2m
m
and the solution for the displacement x is:




n
n
t + B sin
t
where A, B are arbitrary constants.
x = A cos
m
m
58

HELM (2005):
Workbook 19: Dierential Equations

Task

dx
= 0 at t = 0 to nd the unique
Impose the initial conditions x = x0 and
dt
solution to the ODE:

Your solution

Answer



 


dx
n
n
n
n
=
A sin
t +
B cos
t
dt
m
m
m
m

n
dx
= 0 so that
B=0
so that
B = 0.
When t = 0,
dt
m


n
t .
Therefore x = A cos
m
Imposing the remaining initial condition: when t = 0, x = x0 so that x0 = A and nally:


n
x = x0 cos
t .
m

## Case 2: Light damping

If k 2 4mn < 0, i.e. k 2 < 4mn then the roots of the auxiliary equation are complex:

k + i 4mn k 2
k i 4mn k 2
2 =
1 =
2m
2m
Then, after some rearrangement:

## x = ekt/2m [A cos pt + B sin pt] in which p = 4mn k 2 /2m.

HELM (2005):
Section 19.4: Applications of Dierential Equations

59

Task

## If m = 1, n = 1 and k = 1 nd 1 and 2 and then nd the solution for the

displacement x.

Your solution

Answer


1 + i 4 1
3
3
=
= 1/2 i 3/2. Hence x = et/2 A cos
t + B sin
t .
2
2
2
dx
Impose the initial conditions x = x0 ,
= 0 at t = 0 to nd the arbitrary constants and hence nd
dt
the solution to the ODE:
Your solution

Answer
Dierentiating, we obtain



3
3
3
3
3
3
1
dx
= et/2 A cos
t + B sin
t + et/2
A sin
t+
B cos
t
dt
2
2
2
2
2
2
2
At t = 0,
x = x0 = A

(i)

dx
3
1
=0= A+
B
dt
2
2
Solving (i) and (ii) we obtain

3
B=
x0 then
A = x0
3

(ii)

x = x0 et/2

3
3
3
t+
sin
t .
cos
2
3
2

The graph of x against t is shown in Figure 7. This is the case of light damping. As the damping in
the system decreases (i.e. k 0 ) the number of oscillations (in a given time interval) will increase.
In many mechanical systems these oscillations are usually unwanted and the designer would choose a
value of k to either reduce them or to eliminate them altogether. For the choice k 2 = 4mn, known
60

HELM (2005):
Workbook 19: Dierential Equations

x
x0
x0 et/2


x = x0 et/2

3
3
3
t+
sin
t
cos
2
3
2

Figure 7

## Case 3: Heavy damping

If k 2 4mn > 0, i.e. k 2 > 4mn, then there are two real roots of the auxiliary equation, 1 and 2 :

k + k 2 4mn
k k 2 4mn
2 =
1 =
2m
2m
Then
x = Ae1 t + Be2 t .

Task

## If m = 1, n = 1 and k = 2.5 nd 1 and 2 and then nd the solution for the

displacement x.

Your solution

Answer
2.5

6.25 4

= 1.25 0.75
2
Hence 1 , 2 = 0.5, 2 and so x = Ae0.5t + Be2t
=

HELM (2005):
Section 19.4: Applications of Dierential Equations

61

dx
= 0 at t = 0 to nd the arbitrary constants and hence nd
Impose the initial conditions x = x0 ,
dt
the solution to the ODE.
Your solution

Answer
Dierentiating, we obtain
dx
= 0.5Ae0.5t 2Be2t
dt
At t = 0,
x = x0 = A + B

(i)

dx
= 0 = 0.5A 2B
dt

(ii)

1
1
4
B = x0 then x = x0 (4e0.5t e2t ).
A = x0
3
3
3
The graph of x against t is shown below. This is the case of heavy damping.
Solving (i) and (ii) we obtain

x
x0

Other cases are dealt with in the Exercises at the end of the Section.

62

HELM (2005):
Workbook 19: Dierential Equations

## 3. Modelling forced mechanical oscillations

Suppose now that the mass is subject to a force f (t) after the initial disturbance. Then the equation
of motion is
dx
d2 x
+ nx = f (t)
m 2 +k
dt
dt
Consider the case f (t) = F cos t, that is, an oscillatory force of magnitude F and angular frequency
. Choosing specic values for the constants in the model: m = n = 1, k = 0, and = 2 we nd
d2 x
+ x = F cos 2t
dt2

Task

## Find the complementary function for the dierential equation

d2 x
+ x = F cos 2t
dt2
Your solution

Answer
The homogeneous equation is
d2 x
+x=0
dt2
with auxiliary equation 2 + 1 = 0. Hence the complementary function is
xcf = A cos t + B sin t.
Now nd a particular integral for the dierential equation:
Your solution

HELM (2005):
Section 19.4: Applications of Dierential Equations

63

Answer
d2 xp
Try xp = C cos 2t+D sin 2t so that 2 = 4C cos 2t4D sin 2t. Substituting into the dierential
dt
equation gives
(4C + C) cos 2t + (4D + D sin 2t) F cos 2t.
Comparing coecients gives 3C = F and 3D = 0 so that D = 0,
1
xp = F cos 2t. The general solution of the dierential equation is therefore
3
1
x = xp + xcf = F cos 2t + A cos t + B sin t.
3

1
C = F and
3

Finally, apply the initial conditions to nd the solution for the displacement x:
Your solution

Answer
We need to determine the derivative and apply the initial conditions:
dx
2
= F sin 2t A sin t + B cos t.
dt
3
1
At t = 0
x = x0 = F + A and
3
Hence
Then

dx
=0=B
dt

1
A = x0 + F.
3


1
1
x = F cos 2t + x0 + F cos t.
3
3
B=0

and

## The graph of x against t is shown below.

x
x0
t

If the angular frequency of the applied force is nearly equal to that of the free oscillation the
phenomenon of beats occurs. If the angular frequencies are equal we get the phenomenon of
resonance. Note that we can eliminate resonance by introducing damping into the system.

64

HELM (2005):
Workbook 19: Dierential Equations

## 4. Modelling forces on beams

Engineering Example 3
Shear force and bending moment of a beam
Introduction
The beam is a fundamental part of most structures we see around us. It may be used in many ways
depending as how its ends are xed. One end may be rigidly xed and the other free (called cantilevered) or both ends may be resting on supports (called simply supported). Other combinations
are possible. There are three basic quantities of interest in the deformation of beams, the deection,
the shear force and the bending moment.
For a beam which is supporting a load of w (measured in N m1 and which may represent the
self-weight of the beam or may be an external load), the shear force is denoted by S and measured
in N m1 and the bending moment is denoted by M and measured in N m1 .
The quantities M , S and w are related by
dM
=S
dz

(1)

and
dS
= w
(2)
dz
where z measures the position along the beam. If one of the quantities is known, the others can be
calculated from the Equations (1) and (2). In words, the shear force is the negative of the derivative
(with respect to position) of the bending moment and the load is the derivative of the shear force.
Alternatively, the shear force is the negative of the integral (with respect to position) of the load and
the bending moment is the integral of the shear force. The negative sign in Equation (2) reects the
fact that the load is normally measured positively in the downward direction while a positive shear
force refers to an upward force.
Problem posed in words
A beam is xed rigidly at one end and free to move at the other end (like a diving board). It only
has to support its own weight. Find the shear force and the bending moment along its length.
Mathematical statement of problem
A uniform beam of length L, supports its own weight wo (a constant). At one end (z = 0), the
beam is xed rigidly while the other end (z = L) is free to move. Find the shear force S and the
bending moment M as functions of z.
Mathematical analysis
As w is a constant, Equation (2) gives


S = wdz = wo dz = wo z + C.
HELM (2005):
Section 19.4: Applications of Dierential Equations

65

## At the free end (z = L) , the shear force S = 0 so C = wo L giving

S = wo (L z)
This expression can be substituted into Equation (1) to give



wo 2
z + K.
M = Sdz = wo (L z) dz = (wo L wo z) dz = wo Lz
2
wo
Once again, M = 0 at the free end z = L so K is given by K = L2 . Thus
2
wo 2 wo 2
z
L
M = wo Lz
2
2
The diagrams in Figure 8 show the load w (Figure 8a), the shear force S (Figure 8b) and the bending
moment M (Figure 8c) as functions of position z.
Load (w)
w = w0

(a)

Position (z)

L
Shear Force (S)
S = w0 L
(b)

Position (z)

L
Bending Moment (M )

(c)

Position (z)

M = w0 L2

Figure 8: The loading (a), shear force (b) and bending moment (c) as functions of position z
Interpretation
The beam deforms (as we might have expected) with the shear force and bending moments having
maximum values at the xed end and minimum (zero) values at the free end. You can easily
experience this for yourselves: simply hold a wooden plank (not too heavy) at one end with both
hands so that it is horizontal. As you try this with planks of increasing length (and hence weight)
you will nd it increasingly dicult to support the weight of the plank (this is the shear force) and
increasingly dicult to keep the plank horizontal (this is the bending moment).
This mathematical model is an excellent description of real beams.

66

HELM (2005):
Workbook 19: Dierential Equations

Engineering Example 4
Deflection of a uniformly loaded beam
Introduction
A uniformly loaded beam of length L is supported at both ends as shown in Figure 9. The deection
y(x) is a function of horizontal position x and obeys the ordinary dierential equation (ODE)
1
d4 y
(x) =
q(x)
(1)
4
dx
EI
where E is Youngs modulus, I is the moment of inertia and q(x) is the load per unit length at
point x. We assume in this problem that q(x) = q a constant. The boundary conditions are (i) no
deection at x = 0 and x = L (ii) no curvature of the beam at x = 0 and x = L.
Load q
Beam
x

y(x)
x
Ground

## Figure 9: The bending beam, parameters involved in the mathematical formulation

Problem in words
Find the deection of a beam, supported so that that there is no deection and no curvature of the
beam at its ends, subject to a uniformly distributed load, as a function of position along the beam.
Mathematical statement of problem
Find the equation of the curve y(x) assumed by the bending beam that satises the ODE (1). Use
the coordinate system shown in Figure 9 where the origin is at the left extremity of the beam. In
this coordinate system, the boundary conditions, which require that there is no deection at x = 0
and x = L, and that there is no curvature of the beam at x = 0 and x = L, are
(a) y(0) = 0
(b) y(L) = 0
d2 y

(c)
=0
dx2 x=0
d2 y

=0
(d)
dx2 x=L
d2 y

(e)
=0
dx2 x=L
d2 y(x)
dy(x)
are respectively the slope and the radius of curvature of the curve at
and
dx
dx2
point (x, y).
Note that

HELM (2005):
Section 19.4: Applications of Dierential Equations

67

Mathematical analysis
Integrating Equation (1) leads to:
d3 y
(x) = qx + A
dx3
Integrating a second time:

(2)

EI

d2 y
(x) = qx2 /2 + Ax + B
2
dx
Integrating a third time:

(3)

EI

dy
(x) = qx3 /6 + Ax2 /2 + Bx + C
dx
Integrating a fourth time:
EI

(4)

## EIy(x) = qx4 /24 + Ax3 /6 + Bx2 /2 + Cx + D.

(5)

The boundary conditions (a) and (b) enable determination of the constants of integration A, B, C, D.
Indeed, the boundary condition (a), y(0) = 0, and Equation (5) give
EIy(0) = q (0)4 /24 + A (0)3 /6 + B (0)2 /2 + C (0) + D = 0
which yields D = 0.
The boundary condition (b), y(L) = 0, and Equation (5) give
EIy(L) = qL4 /24 + AL3 /6 + BL2 /2 + CL + D.
Using the newly found value for D one writes
qL4 /24 + AL3 /6 + BL2 /2 + CL = 0

(6)

The boundary condition (c) obtained from the denition of the radius of curvature,
Equation (3) give
I

d2 y
(0) = 0, and
dx2

d2 y
(0) = q (0)2 /2 + A (0) + B
dx2

## which yields B = 0 . The boundary condition (d),

d2 y
(L) = 0, and Equation (3) give
dx2

d2 y
(L) = qL2 /2 + AL = 0
dx2
which yields A = qL/2 . The expressions for A, B, D are introduced in Equation (6) to nd the last
unknown constant C. This leads to qL4 /24 qL4 /12 + CL = 0 or C = qL3 /24. Finally, Equation
(5) and the values of constants lead to the solution
EI

## y(x) = [qx4 /24 qLx3 /12 + qL3 x/24]/EI.

(7)

Interpretation
The predicted deection is zero at both ends as required, and you may check that it is symmetrical
about the centre of the beam by switching to the coordinate system (X, Y ) with L/2 x = X
and y = Y and verifying that the deection Y (X) is symmetrical about the vertical axis, i.e.
Y (X) = Y (X).

68

HELM (2005):
Workbook 19: Dierential Equations

Exercises
1. In an RC circuit (a resistor and a capacitor in series) the applied emf is a constant E. Given
dq
= i where q is the charge in the capacitor, i the current in the circuit, R the resistance
that
dt
and C the capacitance the equation for the circuit is
Ri +

q
= E.
C

## If the initial charge is zero nd the charge subsequently.

2. If the voltage in the RC circuit is E = E0 cos t nd the charge and the current at time t.
3. An object is projected from the Earths surface. What is the least velocity (the escape velocity)
of projection in order to escape the gravitational eld, ignoring air resistance.
The equation of motion is
mv

R2
dv
= m g 2
dx
x

where the mass of the object is m, its distance from the centre of the Earth is x and the radius
of the Earth is R.
4. The radial stress p at distance r from the axis of a thick cylinder subjected to internal pressure
dp
= A p where A is a constant. If p = p0 at the inner wall (r = r1 ) and
is given by p + r
dr
is negligible (p = 0) at the outer wall (r = r2 ) nd an expression for p.
5. The equation for an LCR circuit with applied voltage E is
L

1
di
+ Ri + q = E.
dt
C

By dierentiating this equation nd the solution for q(t) and i(t) if L = 1, R = 100, C = 104
and E = 1000 given that q = 0 and i = 0 at t = 0.
6. Consider the free vibration problem in Section 19.4 subsection 2 (page 57) when m = 1, n = 1
and k = 2 (critical damping).
Find the solution for x(t).
7. Repeat Exercise 6 for the case m = 1, n = 1 and k = 1.5 (light damping)
8. Consider the forced vibration problem in Section 19.4 subsection 2 with m = 1, n = 25, k =
8, E = sin 3t, x0 = 0 with an initial velocity of 3.
9. This refers to the Task on page 55 concerning modelling the dissolving of a pill in the stomach.
An alternative model supposes that the pill is very rapidly permeated by stomach acids and the
small granules contained in the capsule dissolve individually. In this case, the rate of change
of volume is assumed to be directly proportional to the volume. Using the experimental data
given in the Task, estimate the time for 95% of the pill to dissolve, based on this alternative
model, and compare results.
HELM (2005):
Section 19.4: Applications of Dierential Equations

69

Answers
1. Use the equation in the form R

q
dq
1
E
dq
+ = E or
+
q= .
dt C
dt RC
R

## The integrating factor is et/RC and the general solution is

q = EC(1 et/RC )

and as

t q EC.

E0 C
cos t et/RC + RC sin t
2
2
2
1+ R C


dq
1 t/RC
E0 C
2
i=
+ RC cos t .
sin t +
=
e
dt
1 + 2 R2 C 2
RC

## 3. vmin = 2gR. If R = 6378 km and g = 9.81 m s2 then vmin = 11.2 km s1 .



r22
p0 r12
1 2
4. p = 2
r1 r22
r
2. q =

5. q = 0.1

1 50t
e
(sin 50 3t + 3 cos 50 3t)
10 3

20
i = e50t sin 50 3t.
3

6. x = x0 (1 + t)et

3
7
7
(cos
t + sin
t)
4
4
7

0.75t

7. x = x0 e
8. x =

1 4t
e (3 cos 3t + 106 sin 3t) 3 cos 3t + 2 sin 3t)
104

dV
1
= kV and V = V0 ekt where k = ln 2. The time taken is about 4 hr
9. This leads to
dt
3
19 min. This is much less than the other model, as should be expected.

70

HELM (2005):
Workbook 19: Dierential Equations